2009
DOI: 10.1203/pdr.0b013e3181991229
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Mutations in the ED1 Gene in Japanese Families With X-Linked Hypohidrotic Ectodermal Dysplasia

Abstract: X-linked hypohidrotic ectodermal dysplasia (XLHED), which is characterized by hypodontia, hypotrichosis, and hypohidrosis, is caused by mutations in ED1, the gene encoding ectodysplasin-A (EDA). This protein belongs to the tumor necrosis factor ligand superfamily. We analyzed ED1 in two Japanese patients with XLHED. In patient 1, we identified a 4-nucleotide insertion, c.119-120insTGTG, in exon 1, which led to a frameshift mutation starting from that point (p.L40fsX100). The patient's mother was heterozygous f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The identification of female carriers of XLHED can be difficult because of the variety of clinical features due to the X-chromosome inactivation, generally that one carrying the wild-type allele [Gunadi et al, 2009]. First, Lexner et al [2007] showed that dental anomalies, salivary flow and composition may be used as a part of a comprehensive clinical examination to identify potential female carries of XLHED [Lexner et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…The identification of female carriers of XLHED can be difficult because of the variety of clinical features due to the X-chromosome inactivation, generally that one carrying the wild-type allele [Gunadi et al, 2009]. First, Lexner et al [2007] showed that dental anomalies, salivary flow and composition may be used as a part of a comprehensive clinical examination to identify potential female carries of XLHED [Lexner et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…Dental abnormalities (hypodontia, microdontia, cone-shaped incisors), mild hypohidrosis, and mild hypotrichosis are the most commonly described signs in female carriers of XLHED [22]. It is widely believed that these linear characteristics of XLHED in female carriers of EDA mutations are the result of preferential inactivation of one X chromosome carrying the wild-type allele [23].…”
Section: Discussionmentioning
confidence: 99%
“…The products were separated and analyzed on a 3730xl Genetic Analyzer (Applied Biosystems, Foster City, CA) using DNA Sequencing Analysis Software (Applied Biosystems, Foster City, CA) [17, 18]. …”
Section: Methodsmentioning
confidence: 99%